Slp‐76 is a critical determinant of NK‐cell mediated recognition of missing‐self targets. Issue 7 (22nd May 2015) - Lampe, Kristin; Endale, Mehari; Cashman, Siobhan; Fang, Hao; Mattner, Jochen; Hildeman, David; Hoebe, Kasper
<x xml:space="preserve">Abstract</x> Absence of MHC class I expression is an important mechanism by which NK cells recognize a variety of target cells, yet the pathways underlying "missing‐self" recognition, including the involvement of activating receptors, remain poorly understood. Using ethyl‐N‐nitrosourea mutagenesis in mice, we identified a germline mutant, designated Ace, with a marked defect in NK cell mediated recognition and elimination of "missing‐self" targets. The causative mutation was linked to chromosome 11 and identified as a missense mutation (Thr428Ile) in the SH2 domain of Slp‐76—a critical adapter molecule downstream of ITAM‐containing surface receptors. The Slp‐76 Ace mutation behaved as a hypomorphic allele—while no major defects were observed in conventional T‐cell development/function, a marked defect in NK cell mediated elimination of β2‐microglobulin (β2M) deficient target cells was observed. Further studies revealed Slp‐76 to control NK‐cell receptor expression and maturation; however, activation of Slp‐76ace/ace NK cells through ITAM‐containing NK‐cell receptors or allogeneic/tumor target cells appeared largely unaffected. Imagestream analysis of the NK‐β2M−/− target cell synapse revealed a specific defect in actin recruitment to the conjugate synapse in Slp‐76ace/ace NK cells. Overall these studies establish Slp‐76 as a critical determinant of NK‐cell development and NK cell mediated elimination of missing‐self target cells in mice.